Data warehouse design for mobile environment - Abu Bakar, Muhamad Shahbani; Ta'a, Azman (2012)
Analysis and design are very important roles in Data Warehouse (DW) system development and forms as a backbone of any successful or failure of the DWproject. The emergence trends of ubiquitous-based application required DW system to be implemented in the mobile environment.However, current analysis and design approaches are based on existing DW environments that focusing on the deployment of DW system in static client-based applications. This will create the limitations on user accessed and reduced the used of analytical information by the decision makers.Consequently, this will prolong the adoption of business intelligence (BI) applications to the users and organisations. This research is to suggest an approach for designing the DW and implement the DW system on the mobile environments.A variant dimension modeling technique will be used to enhance the DW modeling in order to accommodate the requirements of mobile characteristics in the DW design.